Peran Pendidikan Islam dalam Mengatasi Penyakit Sosial Remaja di Era Digital - Nazwa Salsabilla; Adrian Sondak; Ajahari Ajahari (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2026)
The development of digital technology has brought significant changes to the social interaction patterns of teenagers, but on the other hand, it has also given rise to various social issues that impact the character and morals of the younger generation. This research aims to analyze the role of Islamic education in addressing the social issues of teenagers in the digital era and to formulate an Islamic education concept relevant to character building. This research uses a qualitative approach with a type of library research. Data were obtained through a study of various literature sources, such as books, scientific journal articles, previous research findings, and academic documents relevant to the research theme. Data analysis was conducted using content analysis techniques to identify concepts, theories, and findings related to Islamic education and social diseases among adolescents. The research results show that the forms of social diseases most experienced by teenagers in the digital era include cyberbullying, gadget addiction, moral decline, deviant behavior, and exposure to negative content. Islamic education plays a strategic role in addressing these issues thru the internalization of moral values, strengthening spirituality, setting examples, habituating positive behavior, and supervision from the family and school environment. This research concludes that integrative, adaptive Islamic education based on spiritual values and digital ethics can serve as a preventive and curative solution in shaping the character of teenagers in the digital era.